Prevention and Punishment: Barriers to Accessing Health Services for Undocumented Immigrants in the United States - Parul Monga; Allen Keller; Homer Venters (Laws, 2014)
Undocumented immigrants face significant challenges in accessing health care. Throughout the United States, these challenges may relate to the structure of the public health system in which the undocumented find themselves. In addition, local, regional, and national practices aimed at targeting immigrants for deportation or other non-health reasons may serve to punish them for seeking health services or care. Spain and the United Kingdom serve as useful case studies in comparing the ability of the undocumented to seek health services in Europe and the United States. Overall, promoting access to comprehensive health services for the undocumented should be a national priority, along with analysis of any immigration-related laws or policies for potential harmful impact on health care access.